Cryopreservation of Peruvian Paso horse spermatozoa: dimethylacetamide preserved an optimal sperm function compared to dimethyl sulfoxide, ethylene glycol and glycerol. (3rd August 2016) - Santiani, A.; Evangelista‐Vargas, S.; Vargas, S.; Gallo, S.; Ruiz, L.; Orozco, V.; Rosemberg, M.
Abstract : Summary: The objective was to evaluate the effect of different cryoprotectant agents in the cryopreservation of Peruvian Paso horse semen. Twenty semen samples were collected from five Peruvian Paso horse stallions. Each sample was divided into 12 parts to form the groups: dimethylacetamide (DMA), dimethyl sulfoxide (DMSO), ethylene glycol (EG) and glycerol (GLY), at 3%, 4% and 5%. Samples were frozen using a rate‐controlled freezer. Sperm parameters evaluated were motility and viability/acrosomal status. After thawing, progressive motility in DMA group was higher ( p  < .05) than in DMSO, EG and GLY groups. Similarly, viable acrosome‐intact spermatozoa were higher ( p  < .05) using DMA in comparison with DMSO. No differences were found when comparing concentrations for any of the cryoprotectant agents. In conclusion, DMA seems to be a good cryoprotectant agent for the cryopreservation of Peruvian Paso horse stallion semen.